The thymus gland diagnosis and surgical management - Anastasiadis, Kyriakos. (Springer Berlin Heidelberg, 2007)
The critical role of the thymus in the immune system is becoming increasingly well understood. Much of this knowledge is widely dispersed throughout the literature. Although thymectomy is well established as a surgical procedure, these advances need to be made available to the surgeon. Furthermore, neurologists and physicians require a better understanding of the surgical aspects of the thymus. This book, written by selected experts, provides an up-to-date and concise review of the thymus gland for both the surgeon and the physician. Synopsis -- Anatomy -- Changes with aging -- Physiology -- Thymic diseases -- Myasthenia gravis -- Thymus and thymoma in myasthenia gravis patients -- Surgical pathology -- Radiology -- Thymectomy -- Perioperative management for thymectomy -- Systemic treatment of thymoma -- Radiotherapy in the management of thymoma -- Overview of thymic surgery and prospective strategy for thymic diseases.